2022
DOI: 10.1155/2022/4206401
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Status and Development Trend of Aquaculture and Fisheries in Nepal

Abstract: Although Nepal is a landlocked country, it has abundant water resources that enhance its potential for fisheries and aquaculture activities. But, only a few percentages of the total water resources have been utilized properly. Despite a satisfactory growth in pond fish production over the last 15 years with 73,693 Mt. of fish produced in the fiscal year 2020/21, there has not been much significant advancement in the fisheries sector as expected. Some of the major challenges encountered by farmers are lack of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…On the final experimental day, three mahseer were sacrificed and fixed for 24 h in a 10% buffered formalin solution [8]. Afterwards, the fixed samples were kept in 70% ethanol.…”
Section: Vertebral Column Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…On the final experimental day, three mahseer were sacrificed and fixed for 24 h in a 10% buffered formalin solution [8]. Afterwards, the fixed samples were kept in 70% ethanol.…”
Section: Vertebral Column Formationmentioning
confidence: 99%
“…When fish are exposed to a high level of CO 2 , the frequency of skeleton abnormalities increases [7]. It has been demonstrated that acidification influences the incidence of branchiostegal ray deformation and vertebral column malformations, including lordosis [8]. As fry grow into the juvenile stage, their tissues and organs undergo significant changes, along with the calcification of skeletal components, which are necessary for swimming skills and otolith development and vital for equilibrium [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, China has established itself as the top recipient of FDI among developing countries (Agrawal & Khan, 2011). The studies have already identified that Nepal has competitive advantages in areas such as agriculture, water resources (hydropower generation), and tourism (tourism-related hospitality industries) (Dhakal, 2015). Similarly, demographic structure (more than 52% economically active population), gradually improving business indicators (improvement of living standard with increment in the purchasing capacity through the inflow of remittance, etc.…”
Section: Introductionmentioning
confidence: 99%